If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18.1 = p + -7 Reorder the terms: 18.1 = -7 + p Solving 18.1 = -7 + p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. 18.1 + -1p = -7 + p + -1p Combine like terms: p + -1p = 0 18.1 + -1p = -7 + 0 18.1 + -1p = -7 Add '-18.1' to each side of the equation. 18.1 + -18.1 + -1p = -7 + -18.1 Combine like terms: 18.1 + -18.1 = 0.0 0.0 + -1p = -7 + -18.1 -1p = -7 + -18.1 Combine like terms: -7 + -18.1 = -25.1 -1p = -25.1 Divide each side by '-1'. p = 25.1 Simplifying p = 25.1
| v-9.85=6.4 | | 1/2x+2=4x+1/4 | | 27=2a+5 | | 10-x=17 | | 2xy+3yz=-5xz-2xy | | 4z-9z+2=0 | | -(8y+1)-(-7y-5)=5 | | x=-5x^2+6x+9 | | y(x)=-16x^2+64x | | a=2a+(-3) | | 500t=1000/300 | | x=-5x^2+8x+9 | | x^3+x^2+3*x+5=0 | | 2x-(5a+7x)=8x+(-3x+7a)-2a | | 3=j+2 | | f(x)=-5x^2+8x+9 | | 15(m+5)-3(8m+7)= | | 125x^2=12 | | -x^2-6x-8= | | -1=-5+I | | 6+2r-3=6r+3-3r | | 3[7x-2(y-1)]= | | 2=H-4 | | 2=H+4 | | u-1/8 | | -3x^2-6x-8= | | m^2-2*m+2=0 | | 4(x-2)-6(9x+7)= | | z^2-11z+19=-5 | | u-2/4 | | 9x+4x=78 | | x^2-2*m+2=0 |